Download presentation
1
Logical Systems Synthesis
2
Logical Synthesis
3
Basic Gate Synthesis f = a . b f = a + b f = a’
4
Basic Gate Synthesis f = (a . b)’ f = (a + b)’ f = a
5
Operator Precedence in Synthesis
F = A + B . C Incorrect Correct
6
Operator Precedence in Synthesis
F = (A + B) . C Correct Incorrect
7
An example of Step by Step Synthesis Single Output Circuits
8
F = A + (B’ + C)(D’ + BE’) Reducing it to a more abstract form P = BE’ M = B’ + C F = A + M(D’ + P) N = D’ + P F = A + MN Z = MN F = A + Z
9
F = A + Z
10
F = A + Z F = A + MN
11
F = A + Z F = A + MN F = A + M(D’ + P)
12
F = A + (B’ + C)(D’ + BE’)
13
F = A + (B’ + C)(D’ + BE’) F = A + (B’ + C)(D’ + BE’)
14
An example of Multi-Output Synthesis
15
Sharing Gates f = ab + a’c g = ab + a’c’
These are the common terms in both logic expressions, therefore, they can be used to as a common gate when synthesizing the complete digital system. f = ab + a’c g = ab + a’c’
16
Idea of sharing of Gates
f = a’c + ab g = a’c’ + ab Circuits for f and g have a common product term (Implicant) namely ab. We are going to make it a common factor i.e. we are going to use the corresponding gate to drive both outputs f & g.
17
Symbols
18
From Digital Design, 5th Edition by M. Morris Mano and Michael Ciletti
19
Manipulation of Switching Functions
Boolean Algebra Manipulation of Switching Functions Boolean/Logic/Switching Expression/Function
20
Boolean Functions Variables and constants take on only one of the two values : 0 or 1 There are three operators OR written as a + b AND written as a . b NOT written as a ’
21
Operator Precedence () ’ . +
Sequence ’ . +
22
Examples s = ((x . y’ + x’ . y)’ . z) + ((x . y’ + x’ . y) . z’)
c = (x . y’ + x’ . y) . z + x . y c = (((x . y’) + (x’ . y)) . z) + (x . y) f = ( a.b + a.c + b.c’)’ . (a + b + c) + a.b.c f = (((a.b) + (a.c) + (b.c’))’ . (a + b + c)) + (a.b.c)
23
A Theorem about Theorems
Metatheorem A Theorem about Theorems Duality Any Theorem or Identity in Switching Algebra remains true if 0 & 1 are swapped and . & + are swapped throughout the expression Note: Duality does not imply logical equivalence. It only states that one fact leads to another fact.
24
1 + 1 = 1 0 + 0 = 0 0 + 1 = 1 + 0 = 1 x = 1 implies x’ = 0
Axioms / Postulates 0 . 0 = = = = 0 x = 0 implies x’ = 1 1 + 1 = = = = 1 x = 1 implies x’ = 0
25
Theorems (Single Variable)
Null Elements Identities Idempotency Complements Involution x . 0 = 0 x . 1 = x x . x = x x . x’ = 0 (x’)’ = x x + 1 = 1 x + 0 = x x + x = x x + x’ = 1 (x’)’ = x
26
Theorems (2- & 3- Variable)
Commutativity Associativity Distributivity Covering Combining x . y = y . x x . (y . z) = (x . y) . z x . (y + z) = x . y + x . z x + (x . y) = x (x . y) + (x . y’) = x x + y = y + x x + (y + z) = (x + y) + z x + (y . z) = (x + y) . (x + z) x . (x + y) = x (x + y) . (x + y’) = x
27
Theorems (2- & 3- Variable)
DeMorgan’s Theorem Consensus Theorem (x . y)’ = x’ + y’ (x . y) + (x’ . z) + (y . z) = (x . y) + (x’ . z) (x + y)’ = x’ . y’ (x + y) . (x’ + z) . (y + z) = (x + y) . (x’ + z)
28
Theorems (n-Variable)
Generalized Idempotency DeMorgan’s Theorem x . x x = x (x1 . x xn)’ = x1’ + x2’ xn’ x + x x = x (x1 + x xn)’ = x1’ . x2’ xn’
29
Theorems (n-Variable)
Generalized DeMorgan’s Theorem [F(x1, x2, -----, xn, . , + )]’ = F(x1’, x2’, -----, xn’, + , . )
30
Implications of DeMorgan’s Theorem
f = ( a . b )’ = a’ + b’ f = ( a + b )’ = a’ . b’
31
Implications of DeMorgan’s Theorem
f = { [a . ( b’ + c ) ]’ }’ = { a’ + ( b’ + c )’ }’ = { a’ + b . c’ }’ f’ = a’ + ( b . c’ )
32
Function Manipulation
Using Axioms and Theorems of Boolean Algebra
33
Proof of Consensus Theorem
x.y + x’.z + y.z = x.y + x’.z x.y + x’.z + y.z = x.y + x’.z + y.z.1 = x.y + x’.z + y.z.(x + x’) = x.y + x’.z + x.y.z + x’.y.z = x.y + x.y.z + x’.z + x’.y.z = x.y.1 + x.y.z + x’.z.1 + x’.y.z = x.y.(1 + z) + x’.z.(1 + y) = x.y.1 + x’.z.1 = x.y + x’.z Theorem Used a = a.1 1 = a + a’ a.(b + c) = a.b + a.c a.b + a.c = a.(b + c) 1 + a = 1 a.1 = a
34
Find DeMorgan’s Equivalent of the Following
35
DeMorgan’s Equivalent
F = ( ( B . E’ ) + D’ ) . ( B’ + C ) + A = { [ ( ( ( B . E’ ) + D’ ) . ( B’ + C ) ) + A ]’ }’ = { ( ( ( B . E’ ) + D’ ) . ( B’ + C) )’ . A’ }’ = { ( ( B . E’ ) + D’ )’ + ( B’ + C )’ . A’ }’ = { ( B . E’ )’ . D ) + ( B . C’ ) . A’ }’ = { ( B’ + E ) . D ) + ( B . C’ ) . A’ }’ = { ( ( B’ + E ) . D ) ) + ( ( B . C’ ) . A’ ) }’ F = { ( B’ + E ) . D ) + ( B . C’ ) . A’ }’ F’ = ( B’ + E ) . D ) + ( B . C’ ) . A’
36
DeMorgan’s Equivalent F = ( ( B . E’ ) + D’ ) . ( B’ + C ) + A
37
DeMorgan’s Equivalent
F’ = ( B’ + E ) . D ) + ( B . C’ ) . A’
38
Using DeMorgan’s Theorem NAND NOR Inter-Conversion
A circuit developed using NAND gates only can be converted into a circuit employing only NOR gates by directly replacing the NAND gates with the NOR gates and inverting all the inputs and outputs of the circuit The Converse of this operation is also true
39
F = ((((B.E’)’ . D)’ . (B.C’)’)’ . A’)’
40
F’ = ((((B’ + E)’ + D’)’ + (B’ + C)’)’ + A)’
41
Using DeMorgan’s Theorem
Proof by Example Using DeMorgan’s Theorem F = ((((B.E’)’ . D)’ . (B.C’)’)’ . A’)’ = ((((B’ + E) . D)’ . (B’ + C))’ . A’)’ = ((((B’ + E)’ + D’) . (B’ + C))’ . A’)’ = ((((B’ + E)’ + D’)’ + (B’ + C)’) . A’)’ = ((((B’ + E)’ + D’)’ + (B’ + C)’)’ + A) F’ = ((((B’ + E)’ + D’)’ + (B’ + C)’)’ + A)’
42
Can also be written in the following notation
F = A + (B’ + C) . (D’ + B.E’) Can also be written in the following notation F = A + (B’ + C)(D’ + BE’)
43
Forms of Logic Expressions
44
Generalized Forms of Logic Expressions
SOP Sum of Products POS Product of Sums
45
Terminology Literal Sum Term Product Term Product of Sums
Sum of Products
46
Definitions Literal Sum Term Product Term
A variable in either it’s complemented or uncomplemented form Sum Term One or more Literals connected by an OR operator Product Term One or more Literals connected by an AND operator
47
Definitions Product of Sums Sum of Products
One or more Sum Terms connected by an AND operator Sum of Products One or more Product Terms connected by an OR operator
48
SOP Expression
50
POS Expression
52
(A + C)(B + D’)(B’+C)(A + D’ + E)
More SOP Expressions ABC + A’BC’ AB + A’BC’ + C’D’ + D A’B + CD’ + EF + GK + HL’ More POS Expressions (A + B’ + C)(A + C) (A + B’)(A’ + C’ + D)F’ (A + C)(B + D’)(B’+C)(A + D’ + E)
53
Not an SOP or POS Expression
s = (((x . y’) + (x’ . y))’ . z) + (((x . y’) + (x’ . y)) . z’) c = (((x . y’) + (x’ . y)) . z) + (x . y) f = (((a.b) + (a.c) + (b.c’))’ . (a + b + c)) + (a.b.c) nr = ((((b’ + e)’ + d’)’ + (b’ + c)’)’ + a)’ nd = ((((b.e’)’ . d)’ . (b.c’)’)’ . a’)’
54
Canonical Forms of Logic Expressions
C-SOP Sum of Standard Product Terms aka Canonical Sum C-POS Product of Standard Sum Terms aka Canonical Product
55
More Terminology Minterm Maxterm Canonical Sum Canonical Product
56
Definitions Minterm aka Standard Product Term
A Product Term composed of all the variables of the given problem Maxterm aka Standard Sum Term A Sum Term composed of all the variables of the given problem
57
Definitions Canonical Sum Canonical Product
One or more Minterms connected by an OR operator Canonical Product One or more Maxterms connected by an AND operator
58
C-SOP Expression
60
C-POS Expression
62
Writing Algebraic Expressions From Truth Tables
63
Decomposing into Minterms
Implementing 1’s OR =
64
OR = OR = a.b’ + a’.b = f m2 + m1 = f
65
Minterms Notation
67
Expressions involving Minterms
73
Decomposing into Maxterms
Implementing 0’s AND =
74
AND = AND = ( a + b’ ) ( a’ + b ) = f M1 . M2 = f
75
Maxterms Notation
77
Expressions involving Maxterms
83
Write Expressions using Minterm/Maxterm Terminology for the following Truth Table
Using Minterms f = ? Using Maxterms f = ?
84
Write Expressions using Minterm/Maxterm Terminology for the following Truth Table
Using Minterms f = m2 + m5 + m6 Using Maxterms f = M0 . M1 . M3 . M4 . M7
85
Write Expressions using Minterm/Maxterm Terminology for the following Truth Table
Using Minterms f = m2 + m5 + m6 f’ = ? Using Maxterms f = M0 . M1 . M3 . M4 . M7 f’ = ?
86
Write Expressions using Minterm/Maxterm Terminology for the following Truth Table
Using Minterms f = m2 + m5 + m6 f’ = m0 + m1 + m3 + m4 + m7 Using Maxterms f = M0 . M1 . M3 . M4 . M7 f’ = M2 . M5 . M6
87
Write Expressions using Minterm/Maxterm Terminology for the following Truth Table
Using Minterms f = m2 + m5 + m6 f’ = m0 + m1 + m3 + m4 + m7 Using Maxterms f = M0 . M1 . M3 . M4 . M7 f’ = M2 . M5 . M6 Alternative Notation f = ∑ (2, 5, 6) = ∏ (0, 1, 3, 4, 7) f’ = ∏ (2, 5, 6) = ∑ (0, 1, 3, 4, 7)
88
Write Expressions using Minterm/Maxterm Terminology for the following Truth Table
Using Minterms f = ? f’ = ? Using Maxterms f = ? f’ = ?
89
Write Expressions using Minterm/Maxterm Terminology for the following Truth Table
Using Minterms f = m1 + m5 + m6 + m8 + m9 + m10 + m14 + m15 f’ = m0 + m2 + m3 + m4 + m7 + m11 + m12 + m13 Using Maxterms f = M0 . M2 . M3 . M4 . M7 . M11 . M12 . M13 f’ = M1 . M5 . M6 . M8 . M9 . M10 . M14 . M15
90
Write Expressions using Minterm/Maxterm Terminology for the following Truth Table
91
Can you intuitively establish a relationship within the following set of results?
f = m2 + m5 + m6 f’ = m0 + m1 + m3 + m4 + m7 f = M0 . M1 . M3 . M4 . M7 f’ = M2 . M5 . M6 f = m1 + m5 + m6 + m8 + m9 + m10 + m14 + m15 f’ = m0 + m2 + m3 + m4 + m7 + m11 + m12 + m13 f = M0 . M2 . M3 . M4 . M7 . M11 . M12 . M13 f’ = M1 . M5 . M6 . M8 . M9 . M10 . M14 . M15
92
Relationship between Minterms and Maxterms
f = m0 + m3 f = x’ y’ + x y = ( x’ x + y’ x ) ( x’ y + y’ y ) = ( x y’ ) ( x’ y ) f’ = [ (x y’) (x’ y) ]’ = x’ y + x y’ = m1 + m2 f’ = m1 + m2 f = m0 + m3 f = x’ y’ + x y f’ = ( x’ y’ + x y )’ = ( x’ . y’ )’ ( x . y )’ = ( x + y ) ( x’ + y’ ) f’ = ( x + y ) ( x’ + y’ ) = M0 . M3 f’ = M0 . M3 f’ = m1 + m2 = x’ y + x y’ f = ( x’ y + x y’ )’ = ( x’ y )’ ( x y’ )’ = ( x + y’ ) ( x’ + y) = M1 . M2 f = M1 . M2
93
Note : Observe the Duality inherent in this Generalization
To implement a function we can use the logic 1’s in the output to obtain a Minterms’ SOP or use the logic 0’s to obtain a Maxterms’ POS F(x1, x2, …. , xn) = ∑mR = ∏MS [F(x1, x2, …. , xn)]’ = ∑mS = ∏MR Where, T = {Set of all indices} = {0 to 2n - 1} R = {Set of indices of required to implement C-SOP of F(x1, x2, …., xn)} S = T – R Note : Observe the Duality inherent in this Generalization
94
Use Boolean Algebra to establish the relationship between the following set of Expressions
f = m2 + m5 + m6 f’ = m0 + m1 + m3 + m4 + m7 f = M0 . M1 . M3 . M4 . M7 f’ = M2 . M5 . M6 f = m1 + m5 + m6 + m8 + m9 + m10 + m14 + m15 f’ = m0 + m2 + m3 + m4 + m7 + m11 + m12 + m13 f = M0 . M2 . M3 . M4 . M7 . M11 . M12 . M13 f’ = M1 . M5 . M6 . M8 . M9 . M10 . M14 . M15
95
Converting SOP to POS f = x y + x’ z (SOP Form) Using Distributive Law
f = ( x y + x’ ) (x y + z) f = ( x + x’ ) ( y + x’ ) ( x + z ) ( y + z ) f = ( y + x’ ) ( x + z ) ( y + z ) f = ( y + x’ ) ( x + z ) ( y + z ) (POS Form)
96
Converting POS to SOP f = ( x + y ) ( x’ + z ) (POS Form)
Using Distributive Law f = ( x + y ) ( x’ + z ) f = x ( x’ + z ) + y ( x’ + z ) f = x x’ + x z + y x’ + y z f = x z + y x’ + y z f = x z + y x’ + y z (SOP Form) Note : To obtain the expression f = x y + x’ z as in the previous slide apply Consensus Theorem
97
Converting SOP to C-SOP
F = A + B’C (SOP Form) Expanding both terms separately using {x = x . 1} & {1 = (x + x’)} A = A (B + B’) = AB + AB’ = AB (C + C’) + AB’ (C + C’) A = ABC + ABC’ + AB’C + AB’C’ B’C = B’C (A + A’) = AB’C + A’B’C Combining the expressions F = ABC + ABC’ + AB’C + AB’C’ + AB’C + A’B’C = ABC + ABC’ + AB’C + AB’C + AB’C’ + A’B’C Using {x + x = x} F = ABC + ABC’ + AB’C + AB’C’ + A’B’C F = ABC + ABC’ + AB’C + AB’C’ + A’B’C (C-SOP Form)
98
Converting POS to C-POS
f = ( x’ + y ) ( x + z ) ( y + z ) (POS Form) Expanding the three terms separately using {x = x + 0} & {0 = x x’} ( x’ + y ) = x’ + y + z z’ = ( x’ + y + z ) ( x’ + y + z’ ) ( x + z ) = x + z + y y’ = ( x + z + y ) ( x + z + y’ ) = ( x + y + z ) ( x + y’ + z ) ( y + z ) = y + z + x x’ = ( y + z + x ) ( y + z + x’ ) = ( x + y + z ) ( x’ + y + z ) Combining the expressions f = ( x’ + y + z ) ( x’ + y + z’ ) ( x + y + z ) ( x + y’ + z ) ( x + y + z ) ( x’ + y + z ) f = ( x’ + y + z ) ( x’ + y + z ) ( x + y + z ) ( x + y + z ) ( x’ + y + z’ ) ( x + y’ + z ) Using {x . x = x} f = ( x’ + y + z’ ) ( x + y + z ) ( x’ + y + z’ ) ( x + y’ + z ) f = ( x’ + y + z’ ) ( x + y + z ) ( x’ + y + z’ ) ( x + y’ + z ) (C-POS Form)
Similar presentations
© 2024 SlidePlayer.com Inc.
All rights reserved.